A mesoporous silica nanoparticle with charge-convertible pore walls for efficient intracellular protein delivery - Park, Hee Sung; Kim, ChanWoo; Lee, Hong Jae; Choi, Ji Hye; Lee, Se Geun; Yun, Young-Pil; Kwon, Ick Chan; Lee, Seung Jin; Jeong, Seo Young; Lee, Sang Cheon (IOP PUBLISHING LTD, 2010)
We report a smart mesoporous silica nanoparticle (MSN) with a pore surface designed to undergo charge conversion in intracellular endosomal condition. The surface of mesopores in the silica nanoparticles was engineered to have pH-hydrolyzable citraconic amide. Solid-state nuclear magnetic resonance (NMR), Fourier-transform infrared (FT-IR) spectroscopy, and Brunauer-Emmett-Teller (BET) analyses confirmed the successful modification of the pore surfaces. MSNs (MSN-Cit) with citraconic amide functionality on the pore surfaces exhibited a negative zeta potential (-10 mV) at pH 7.4 because of the presence of carboxylate end groups. At cellular endosomal pH (similar to 5.0), MSN-Cit have a positive zeta potential (16 mV) indicating the dramatic charge conversion from negative to positive by hydrolysis of surface citraconic amide. Cytochrome c (Cyt c) of positive charges could be incorporated into the pores of MSN-Cit by electrostatic interactions. The release of Cyt c can be controlled by adjusting the pH of the release media. At pH 7.4, the Cyt c release was retarded, whereas, at pH 5.0, MSN-Cit facilitated the release of Cyt c. The released Cyt c maintained the enzymatic activity of native Cyt c. Hemolytic activity of MSN-Cit over red blood cells (RBCs) was more pronounced at pH 5.0 than at pH 7.0, indicating the capability of intracellular endosomal escape of MSN carriers. Confocal laser scanning microscopy (CLSM) studies showed that MSN-Cit effectively released Cyt c in endosomal compartments after uptake by cancer cells. The MSN developed in this work may serve as efficient intracellular carriers of many cell-impermeable therapeutic proteins.
Keywords: RESPONSIVE CONTROLLED-RELEASE; CARRIER SYSTEM; PH; FUNCTIONALIZATION; POLYMER